Implementasi Program Asistensi Mengajar Berbasis Praktik Reflektif sebagai Inovasi Kurikulum Outcome-Based Education (OBE) untuk Penguatan Konektivitas Karir Lulusan PGSD - Raihan, Siti; Sinta Nurul Oktaviana Kasim; Freddi Sarman; Affan Yusra; Yulianti (Kreasi: Jurnal Inovasi dan Pengabdian kepada Masyarakat, 2025)
The transformation of higher education in Indonesia requires teacher education institutions (LPTKs) to ensure that graduates’ learning outcomes are aligned with professional demands and career readiness. The Department of Primary School Teacher Education (PGSD) must therefore design a curriculum that not only emphasizes theoretical mastery but also strengthens students’ career connectivity as prospective professional teachers. This community service program aimed to implement Teaching Assistance in Elementary Schools (AMSD) based on reflective practice as a curriculum innovation within the Outcome-Based Education (OBE) framework to enhance the career connectivity of PGSD graduates. The specific objectives were: (1) to improve students’ ability to design, implement, and reflect on reflective teaching practices in elementary schools, and (2) to strengthen the integration between departmental learning outcomes and professional teacher career profiles based on John Holland’s career theory (RIASEC). The program was conducted during the odd semester of the 2025/2026 academic year at SD Islam Terpadu Al Fatih, Makassar City, involving 10 fifth-semester PGSD students. The implementation used participatory, reflective, and collaborative approaches through four stages: needs analysis, reflective training and workshop, school-based AMSD implementation, and final reflective evaluation. Data were collected through Reflective Teaching Journals, reflective assessment rubrics, and the RIASEC career orientation instrument. The results indicated a 26.7% increase in students’ reflective ability, a 23% improvement in their understanding of OBE principles, and strengthened career orientation predominantly in the Social and Artistic types, consistent with the professional characteristics of elementary school teachers. The collaboration between lecturers, mentor teachers, and students fostered a reflective learning ecosystem that enhanced pedagogical competence, career awareness, and teacher professionalism. This program demonstrates that reflective-based AMSD serves as an effective OBE curriculum innovation to reinforce PGSD graduates’ career connectivity. The model is recommended for replication in other partner schools as a strategic approach to cultivating a reflective professional culture in teacher education.